Alasan Malaysia Menghentikan Impor Sampah Plastik Tahun 2018 - Yodisari, Ni Wayan Rahayuni; Dharmiasih, D.A. Wiwik; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
This research aims to describe the reason for Malaysia to stop importing plastic waste in 2018 by using a qualitative method. The import of Malaysia plastic waste is part of a foreign policy that has been going on for years to meet the need for secondary raw materials for several industrial sectors, especially manufacturing. Although the import of plastic waste has been carried out  by  Malaysia for many years and provides economic benefits. However, Malaysia ultimately chose to end its foreign policy regarding plastic waste imports in 2018. Therefore, Researcher uses one theory and one concept, which are foreign policy theory and economic security in order to answer the motive behind Malaysia to stop importing plastic waste in 2018. This research perceives that Malaysia’s issued a foreign policy to stop the import of plastic waste has been based on considerations and reasons for achieving economic security.   Keywords: Malaysia, Economic Security, Foreign Policy, Import Cessation